2012
DOI: 10.1016/j.neuroscience.2012.07.045
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of astrocyte-derived 14,15-epoxyeicosatrienoic acid on hydrogen peroxide-induced cell injury in astrocyte-dopaminergic neuronal cell line co-culture

Abstract: Astrocytes perform several functions that are essential for normal neuronal activity. They play a critical role in neuronal survival during ischemia and other degenerative injuries and also modulate neuronal recovery by influencing neurite outgrowth. In this study, we investigated the neuroprotective effects of astrocyte-derived 14,15-epoxyeicosatrienoic acid (14,15-EET), metabolite of arachidonic acid by Cytochrome P450 epoxygenases (CYP), against oxidative stress induced by hydrogen peroxide (H2O2). We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
4
31
0
1
Order By: Relevance
“…The reason for the region-dependent effect is not known, nor is it known why sEHI exerts differential effects on astrocytes versus microglial cells. The sEH enzyme is localized to astrocytes (Marowsky et al , 2009; Rawal et al , 2009; Sura et al , 2008) where it is thought to regulate levels of epoxy fatty acids in the brain (Marowsky et al, 2009; Terashvili et al , 2012), but there is very little information regarding the expression or function of sEH in microglial cells. Similarly, there is little known about the effect of sEH inhibition on the activational status of either astrocytes or microglial cells with the exception of a recent report that pharmacologic inhibition of sEH alters the transcriptional profile of activated microglia to selectively induce anti-inflammatory and neuroprotective cytokine expression (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the region-dependent effect is not known, nor is it known why sEHI exerts differential effects on astrocytes versus microglial cells. The sEH enzyme is localized to astrocytes (Marowsky et al , 2009; Rawal et al , 2009; Sura et al , 2008) where it is thought to regulate levels of epoxy fatty acids in the brain (Marowsky et al, 2009; Terashvili et al , 2012), but there is very little information regarding the expression or function of sEH in microglial cells. Similarly, there is little known about the effect of sEH inhibition on the activational status of either astrocytes or microglial cells with the exception of a recent report that pharmacologic inhibition of sEH alters the transcriptional profile of activated microglia to selectively induce anti-inflammatory and neuroprotective cytokine expression (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of cytoprotection in neuronal and lung epithelial cells by its potent antioxidant propensity was evaluated by estimating the biomarkers known to be induced by oxidative stress. H 2 O 2 is a well known potent inducer of ROS capable of inducing cell injury both in vitro and in vivo (Kim et al 2012;Terashvili et al 2012). Studies have shown that H 2 O 2 is known to induce oxidative damage, leading to lipid peroxidation, ROS generation, GSH depletion and reduction in mitochondrial membrane potential, antioxidant enzymes (SOD, catalase and GPx) activity preceding cell death (Chan et al 2009;Brenner et al 2010;Gulden et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…14,15-EET stimulates axon growth in primary cortical and sensory neuron cultures [154], and EETs mediate cerebral vasodilation produced by stimulation of astrocyte metabotropic glutamate receptors, possibly by activating K + channels or TRPV4 channels [114,155,156]. When injected into the rat brain, 14,15-EET produced an anti-nociceptive effect through activation of β-endorphin and met-enkephalin [157], and it reduced the injurious effect of H 2 O 2 in the dopaminergic N27 neuronal cell line [158]. The administration of sEH inhibitors delayed the onset of seizures mediated by GABA, indicating that EET stabilization can suppress pathologic neurotransmission in the brain [159].…”
Section: Physiological Functions Of Pufa Epoxidesmentioning
confidence: 99%